Navigating evangelical affect: convictions, promises, and dissonance in adolescent adherence to purity teachings - Schultz, Olivia J. (Theology & sexuality, 2023)
This paper theorizes how evangelicalism utilizes affect to convict adolescents to adhere to evangelical purity teachings, despite a proliferation of scholarship and lived experiences demonstrating disaffected outcomes. It contends that evangelicalism entices youth with captivating affect, promising a blissful marriage, meaningful participation in a divinely good movement, and assured salvation in exchange for obedience. Conversely, disobedience carries the explicit consequences of unhappiness, sin, and the threat of hell. Sara Ahmed's insights on collective emotions and the promise of happiness reveal that evangelicalism attaches positive affect to the social norms it aims to perpetuate, rather than those genuinely conducive to happiness. In the process of internalizing affective evangelical rhetoric claiming that evangelicalism is inherently good, adolescents learn not to see, or experiencing a lack of capacity to see, the negative outcomes that is inherent to evangelical beliefs and its projects.